2018
DOI: 10.3758/s13420-018-0367-5
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition in dogs: Do dogs know they could be wrong?

Abstract: In the current study, we investigated the question of whether dogs were sensitive to the information that they themselves had or had not acquired. For this purpose, we conducted three consecutive experiments in which dogs had to find a reward that was hidden behind one of two V-shaped fences with a gap at the point of the V. This setup allowed us to distinguish between selecting one of the fences by walking around it and seeking additional information by checking through the gap in the fence. We varied whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 59 publications
(114 reference statements)
4
30
1
5
Order By: Relevance
“…Most critically, Burton never took the opportunity to look through the transparent section of the apparatus during seen or unseen trials. This finding is consistent with previous tests of metacognition in domestic dogs [23,24] that required an operant response, such as pushing a lever, but not consistent with [25], in which dogs could simply look through a gap before travelling past it to obtain the reward. Burton did not seek information when he should have been uncertain.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Most critically, Burton never took the opportunity to look through the transparent section of the apparatus during seen or unseen trials. This finding is consistent with previous tests of metacognition in domestic dogs [23,24] that required an operant response, such as pushing a lever, but not consistent with [25], in which dogs could simply look through a gap before travelling past it to obtain the reward. Burton did not seek information when he should have been uncertain.…”
Section: Discussionsupporting
confidence: 91%
“…Prior work with domestic dogs has shown that dogs accurately select a baited container at above chance levels when they witnessed the baiting of the container, but at or below chance levels when they did not witness the baiting of the container [23,24]. Although in one study, dogs were above chance on unseen trials as well, dogs also utilized the option to look for helpful information in that study [25]. Although Burton had passed criterion during knowledge testing, his accuracy was below chance levels for both seen and unseen trials during testing, which suggests challenges with the testing situation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Two studies with dogs found that they did not seek information about the location of food when they had not seen where it was placed (Bräuer et al 2004), but rather sought information from human informants (McMahon et al 2010). A more recent study found that dogs sought information about a hidden food reward or toy more often when they had not seen which of two barriers it was placed behind and when the food was higher-value, though their search behaviour did not change with longer delays (Belger and Brauer 2018).…”
Section: Introductionmentioning
confidence: 99%